Acute Kidney Injury in Very Preterm Infants: A Cohort Study in a Level III NICU - Guzoglu, Niluefer; Tandircioglu, Umit Aye; Bulut, Aye; Acar, Banu Celikel; Aliefendioglu, Didem (Galenos Publ House, 2024)
BACKGROUND/AIMS: Acute kidney injury (AKI) is not rare among preterm infants in neonatal intensive care units (NICU). It raises mortality and morbidity in NICUs and also chronic kidney disease in the long term. The aim of this study was to define the incidence of clinical characteristics and the course of AKI in very preterm infants. MATERIALS AND METHODS: A retrospective cohort study was conducted in a level III NICU in a university hospital. All very preterm infants born in the same hospital during the study period were included in this study. Patient data were taken from the medical records. AKI diagnosis was made using the neonatal-modified Kidney Disease Improving Global Outcomes (KDIGO) criteria. RESULTS: AKI was diagnosed in 20 very preterm infants (42%). The median time of AKI diagnosis was 4.5 days of life (between 2-12 days). While there were 8 infants with AKI when the diagnosis was made based on the serum creatinine (Cr) level being over 1.5, the diagnosis of AKI increased to 20 with the use of the KDIGO criteria. Need for resuscitation in the birth room, patent ductus arteriosus, the number of cases of apnea, desaturation episodes, sepsis, hypotension, inotropic support, and sepsis rates were significantly higher in the AKI group. Days hospitalized among survivors were longer and mortality was higher in the AKI group than in the non-AKI group (p=0.042, p<0.0001 respectively). CONCLUSION: The neonatal KDIGO criteria are beneficial and also informative in diagnosing and staging AKI. Close follow-up of urine output and Cr levels especially in the first days is essential in very preterm infants.
Keywords: Acute kidney injury; preterm; creatinine